A method for recycling a battery to prepare a long-cycle polyanionic sodium electric positive electrode material

CN122968481APending Publication Date: 2026-10-23JIANGXI LONGKAI PILOT PLATFORM CIRCULATION TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610834131.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]本发明的目的在于解决现有磷酸铁锂电池回收废渣处理成本高、铁磷资源利用率低、固废污染严重的问题,同时克服传统化学试剂合成NFPP材料成本高、易产生杂相、电化学性能不佳的技术缺陷,提供一种以电池回收废渣为原料制备长循环、高纯度、高性能NFPP聚阴离子型钠离子电池正极材料的方法,实现固废变废为宝、资源化高效利用,同时大幅降低钠电正极材料生产成本

Benefits of technology

[0013]上述方案中,彻底解决锂电池沉锂废渣处置难题,废渣中Fe、P元素回收利用率≥95%,无二次固废产生,每吨废渣可制备20~30kg高性能NFPP正极材料,实现工业固废资源化高效利用,大幅降低电池回收企业环保成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968481A_ABST
    Figure CN122968481A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing long-cycle polyanion sodium electric positive electrode material by recycling batteries, and belongs to the technical field of battery solid waste resource utilization and sodium ion battery electrode material. The method takes iron and phosphorus-containing waste residues generated after recycling lithium carbonate from lithium iron phosphate positive electrodes as core raw materials, and is subjected to acid dissolution, iron valence state unification oxidation, component precise regulation, controllable precipitation of iron hydrogen phosphate precursor, separation and drying, proportioning and mixing, spray forming and high-temperature calcination processes. The application solves the industry pain points of low resource utilization rate, high environmental protection disposal cost of traditional lithium battery recycling waste residues, high chemical reagent synthesis cost of commercial NFPP materials, easy generation of impurities, and poor cycle stability. The application adds a phosphoric acid stabilizer to inhibit iron ion hydrolysis, unifies the single valence state of trivalent iron, accurately regulates the iron-phosphorus molar ratio to 3:4, and obtains an amorphous precursor with atomic-level uniform mixing, effectively prevents the generation of impurities, and improves the material compaction density and structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of battery solid waste resource utilization and sodium-ion battery electrode materials, specifically relating to a method for preparing long-cycle polyanionic sodium battery cathode materials by battery recycling. Background Technology

[0002] Lithium-ion batteries are widely used in new energy vehicles, energy storage power stations, and consumer electronics. With the large-scale retirement of power and energy storage batteries, the resource recycling of retired lithium iron phosphate batteries has become an industry necessity. Currently, the mainstream recycling process involves acid leaching and impurity removal of retired lithium iron phosphate cathode powder, followed by precipitation of lithium ions from the leachate using sodium carbonate to produce lithium carbonate products, thus achieving lithium resource recovery. However, this process generates a large amount of industrial waste containing iron and phosphorus, primarily Fe. 2+ / Fe 3+ PO4 3- At the same time, a small amount of Na remains. + SO4 2- Cl - Impurities such as iron and phosphorus are present. Currently, this type of waste is mainly disposed of through landfill and low-cost, extensive treatment, which not only causes a serious waste of core resources such as iron and phosphorus, but also significantly increases the environmental disposal costs of battery recycling companies, thus hindering the green and low-cost development of the power battery recycling industry.

[0003] Sodium-ion batteries, due to the abundance of sodium resources, low cost, and excellent safety performance, are the most promising electrochemical energy storage devices for large-scale energy storage and low-speed power applications. Among them, the polyanionic Na4Fe3(PO4)2P2O7 (NFPP) cathode material has a three-dimensional stable crystal structure, excellent low-temperature performance, ultra-long cycle life, and high structural stability, making it one of the core cathode materials for high-performance sodium-ion batteries.

[0004] Existing NFPP material preparation technologies all employ high-purity chemical reagents for synthesis. Iron sources are primarily ferrous sulfate, ferric nitrate, and ferric phosphate; phosphorus sources are ammonium dihydrogen phosphate and phosphoric acid; sodium sources are sodium carbonate and sodium acetate; and carbon sources are glucose and citric acid. Preparation methods include sol-gel, hydrothermal, and traditional solid-state methods. These processes have significant drawbacks: First, the high cost of high-purity chemical reagents significantly increases the production cost of NFPP materials, weakening the low-cost advantage of sodium-ion batteries. Second, the synthesis process is complex, with poor reaction controllability, and the products are prone to the formation of impurity phases such as Fe2O3 and Fe3O4, which damage the material's structural integrity and reduce its specific capacity and cycle stability. Third, the process has low added value, making it impossible to achieve solid waste resource utilization, resulting in extremely low resource utilization rates.

[0005] To address the dual industry pain points of resource waste and high environmental pressure from existing battery recycling waste, as well as the high cost and unstable performance of NFPP cathode materials, this paper proposes a process for the low-cost, large-scale preparation of high-cycle-stability NFPP sodium cathode materials using lithium battery recycling waste. This process has significant engineering, economic, and environmental value. Summary of the Invention

[0006] The purpose of this invention is to solve the problems of high cost of treating recycled lithium iron phosphate battery residue, low utilization rate of iron and phosphorus resources, and serious solid waste pollution. At the same time, it overcomes the technical defects of traditional chemical reagent synthesis of NFPP materials, such as high cost, easy generation of impurity phases, and poor electrochemical performance. This invention provides a method for preparing long-cycle, high-purity, and high-performance NFPP polyanionic sodium-ion battery cathode materials using recycled battery residue as raw material, realizing the transformation of solid waste into treasure and efficient resource utilization, while significantly reducing the production cost of sodium battery cathode materials.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution: To achieve the above-mentioned objectives, this invention provides a method for preparing long-cycle polyanionic sodium cathode materials from battery recycling. The core method uses iron-phosphorus-containing waste residue from the recovery of lithium carbonate from lithium iron phosphate cathodes as raw material. The process involves uniform valence state, composition control, controlled precipitation, spray molding, and high-temperature calcination to prepare high-purity NFPP cathode materials. The specific steps are as follows: 1. Waste residue pretreatment and valence state unification: Collect the residual waste residue after acid leaching, impurity removal, and sodium carbonate precipitation of lithium iron phosphate cathode. Dissolve it completely in hydrochloric acid or sulfuric acid to obtain a leachate containing mixed valence states of iron and phosphate. Add hydrogen peroxide, sodium hypochlorite, or introduce air as an oxidant to the leachate to remove all Fe from the system. 2+ Oxidized to Fe 3+ This eliminates the problem of uneven product composition caused by mixed valence state iron; then, soluble iron salts such as ferric sulfate and ferric nitrate or phosphoric acid are added to precisely control the iron and phosphorus concentrations in the system, providing a stable component basis for subsequent precise precipitation and inhibiting the side reaction of iron ion hydrolysis.

[0008] 2. Precise and controllable precipitation preparation of precursors: The oxidized leachate is heated to 40–80°C, and a small amount of phosphoric acid is added as a stabilizer under stirring. Fe is fixed through the complexation stabilization effect of phosphoric acid. 3+ This process completely eliminates the formation of colloidal Fe(OH)3 precipitate. Subsequently, ammonium phosphate solution is slowly added dropwise, and the pH of the system is precisely adjusted to 2.0–4.0 using dilute ammonia or dilute acid. After a complete reaction at a constant temperature, the mixture is aged for 1–3 hours to generate ferric hydrogen phosphate precipitate with a strict iron-to-phosphorus molar ratio of 3:4. This precipitate has an amorphous structure, with iron and phosphorus atoms uniformly mixed at the molecular level, thus preventing the formation of impurity phases in subsequent NFPP products from the outset.

[0009] 3. Precursor separation and purification: The solid precipitate of the reaction mixture is separated by vacuum filtration or centrifugation. The surface-adsorbed impurity ions are removed by washing with deionized water multiple times. The mixture is then dried at 105℃ for 6-8 hours to obtain high-purity ferric hydrogen phosphate precursor powder with precise composition.

[0010] 4. Ingredient preparation and spray molding: According to the stoichiometric ratio of Fe:P=3:4 and Na:Fe=4:3, the ferric hydrogen phosphate precursor is mixed with sodium carbonate, with an appropriate excess of 1% to 3% of sodium carbonate to ensure complete sodiumization; glucose and citric acid are added as carbon sources to provide subsequent carbon coating modification; deionized water is added and the mixture is high-speed milled for 2 hours to prepare a uniform and stable slurry; the slurry is then spray-dried to prepare spherical precursor powder, the spherical structure of which can improve the compaction density and structural stability of the material.

[0011] 5. High-temperature calcination molding: The spray-dried spherical precursor powder is placed in an argon inert atmosphere and heated to 550-700℃ at a rate of 5℃ / min. The temperature is maintained for 4-8 hours. After the high-temperature solid-phase reaction, the powder is naturally cooled and then gas-crushed and sieved to obtain pure-phase, long-cycle NFPP polyanion sodium-ion battery cathode material.

[0012] The core innovation of this invention is that traditional processes, through direct precipitation, easily produce problems such as ferric hydroxide colloids, an imbalance in the iron-phosphorus ratio, numerous impurity phases in the product, and poor recycling. This invention addresses these issues by using Fe... 2+ The three core technologies of complete oxidation of the unified single valent iron, pre-addition of phosphoric acid stabilizer to inhibit hydrolysis, and precise control of the 3:4 iron-phosphorus stoichiometric ratio precipitation are used to obtain a highly active precursor with precise composition and uniform mixing. The final NFPP material is free of impurities, has uniform particles and a dense structure, and has both high specific capacity and ultra-long cycle stability, while completely realizing the resource utilization of waste residue. Compared with the prior art, the present invention has at least the following beneficial effects:

[0013] The above solution completely solves the problem of lithium battery lithium residue disposal. The Fe and P elements in the residue are recycled at a rate of ≥95%, with no secondary solid waste generated. Each ton of residue can be used to prepare 20-30 kg of high-performance NFPP cathode material, realizing the efficient utilization of industrial solid waste resources and significantly reducing the environmental protection costs of battery recycling companies.

[0014] The above scheme abandons the traditional high-purity chemical reagent raw material system and uses industrial solid waste as the core raw material. It does not require expensive iron or phosphorus sources. Compared with the traditional synthesis process, the overall production cost of materials is reduced by 30% to 50%, which greatly enhances the low-cost competitive advantage of sodium-ion batteries.

[0015] In the above scheme, the NFPP material prepared by the present invention has a pure phase sodium iron pyrophosphate structure, without impurity phases such as Fe2O3 and Fe3O4, with uniform particle size (200-500nm), dense particles, and high compaction density; it has excellent electrochemical performance, with an initial specific capacity of 115-126mAh / g at 0.1C rate, a capacity retention rate of ≥90% after 500 cycles at 1C high rate, and an optimal sample cycle retention rate of 96.2%; the specific capacity can still reach 108mAh / g at 5C high rate. It has the excellent characteristics of high capacity, high rate, and long cycle, and its performance is comparable to commercially available materials synthesized from pure reagents.

[0016] The above scheme features a simple and controllable process with strong stability and good repeatability. It does not involve complex reaction equipment and the process of spray molding combined with high-temperature calcination is suitable for large-scale industrial production, making it highly feasible for industrialization. Attached Figure Description

[0017] The accompanying drawings, which are incorporated herein and form part of the specification, illustrate embodiments of the present disclosure and, together with the specification, further serve to explain the principles of the present disclosure and enable those skilled in the art to implement and use the present disclosure.

[0018] Figure 1 The X-ray diffraction (XRD) pattern of the NFPP material prepared in Example 1 of this invention shows that the pattern has no impurity peaks, proving that the product is a pure phase Na4Fe3(PO4)2P2O7 polyanionic structure with excellent crystallinity.

[0019] Figure 2 The image shows a scanning electron microscope (SEM) image of the NFPP material prepared in Example 1 of this invention. The material particles are uniform in size, with a particle size concentrated in the range of 200-500 nm. The particles have regular morphology, good dispersibility, and dense structure.

[0020] Figure 3 This is a table comparing the electrochemical performance of NFPP materials in various embodiments and comparative examples of the present invention. Detailed Implementation

[0021] The present invention will be further described in detail below with reference to specific embodiments. The present invention is not limited to these embodiments. All equivalent improvements and substitutions based on the process principle of the present invention shall fall within the protection scope of the present invention.

[0022] The raw materials described in this invention are all conventional industrial raw materials, and the testing equipment and electrochemical testing methods used are all industry-standard methods. Example

[0023] A method for preparing long-cycle polyanionic cathode materials from battery recycling, comprising the following specific steps: 1. Leachate preparation and valence state control: 5 L of acid-soluble leachate from the waste residue after lithium iron phosphate precipitation was taken, and the components were analyzed: total iron concentration 0.25 mol / L (Fe). 2+ Accounting for 60%, Fe 3+ (40% of the sample was used), P concentration 0.23 mol / L, pH=2.8; 50 mL of 30% hydrogen peroxide was added under stirring, and oxidation was carried out for 30 min to remove Fe. 2+ Completely oxidized to Fe 3+ Add ferric sulfate solid to adjust Fe 3+ The concentration was adjusted to 0.40 mol / L, and phosphoric acid was added to adjust the total P concentration to 0.50 mol / L to obtain a stable pretreated leachate.

[0024] 2. Precursor precipitation: Take 1L of pretreated leachate and heat it to 60℃; add 2mL of 85% phosphoric acid as a stabilizer and stir evenly; prepare a 1.0mol / L ammonium phosphate solution, slowly add 0.53mol ammonium phosphate solution, and adjust the pH of the system to 2.5-3.0 with dilute ammonia water at the same time. After constant temperature reaction, age for 2h to generate a yellowish-brown ferric hydrogen phosphate precipitate.

[0025] 3. Separation and drying: The precipitate system was vacuum filtered, washed four times with deionized water, and dried at 105℃ for 8 hours to obtain the ferric hydrogen phosphate precursor. ICP analysis showed that the Fe:P molar ratio was 3:3.99, which is close to the theoretical stoichiometric ratio.

[0026] 4. Spray drying of ingredients: Take 10.00g of precursor, add 12.80g of sodium carbonate (1% excess), 1.5g of glucose, and 200mL of deionized water. Ball mill and mix for 2 hours to obtain a uniform slurry. Spray drying parameters: inlet temperature 180℃, outlet temperature 100℃, feed rate 10mL / min to obtain spherical precursor powder.

[0027] 5. High-temperature calcination: The spherical precursor is placed in an argon atmosphere, heated to 600℃ at a rate of 5℃ / min, held at that temperature for 6 hours, and then naturally cooled and sieved to obtain the NFPP cathode material.

[0028] Performance testing: Initial specific capacity at 0.1C is 119mAh / g, capacity retention rate after 500 cycles at 1C is 92.5%, the material has a pure phase structure and uniform and dense particles.

[0029] Comparative Example 1 The process steps are basically the same as those in Example 1, except that in step (2), the phosphoric acid stabilizer is not added in advance, and the ammonium phosphate solution is added directly.

[0030] Experimental results: During the dropwise addition process, a large amount of reddish-brown ferric hydroxide colloidal precipitate was rapidly generated, making filtration and washing extremely difficult; the precursor Fe:P = 3:5.2, with the composition significantly deviating from the theoretical value; the XRD pattern of the calcined product showed obvious Fe2O3 impurity peaks; the electrochemical performance declined sharply, with an initial specific capacity of only 85 mAh / g at 0.1C and a capacity retention of only 72% after 500 cycles at 1C. This demonstrates that pre-added phosphoric acid stabilizes Fe. 3+ Suppressing hydrolysis is key to preparing high-purity, high-performance materials. Example

[0031] 1. Waste residue pretreatment: Same as in Example 1, adjusting the Fe content of the leachate. 3+ Concentration 0.30 mol / L, P concentration 0.38 mol / L.

[0032] 2. Precipitation process: Precipitation temperature 40℃, pH controlled at 2.0~2.5, ammonium phosphate added at 1.05 times the theoretical value, aged for 3h, to obtain the precursor Fe:P=3:4.02.

[0033] 3. Separation and drying: Same as in Example 1.

[0034] 4. Ingredient preparation and molding: Only sodium carbonate is added in the metered ratio, without adding a carbon source. After ball milling, spherical powder is prepared using the same spray drying process.

[0035] 5. Calcination process: The finished product is obtained by calcining at 700℃ for 4 hours under an argon atmosphere.

[0036] Performance testing: Initial specific capacity at 0.1C is 122mAh / g, capacity retention rate is 91.8% after 500 cycles at 1C, and the spherical morphology effectively improves the cycling stability of carbon-free materials.

[0037] Comparative Example 2 (Unoxidized Fe) 2+ ) The process steps are basically the same as those in Example 1, except that step (1) does not involve hydrogen peroxide treatment, but instead directly adds ferrous sulfate and phosphoric acid to adjust the parameters.

[0038] Experimental results: The system contains iron in mixed valence states. Fe was observed during precipitation, washing, and calcination. 2+ It is easily oxidized, leading to uneven precursor composition (Fe:P = 3:3.7); the calcined product contains Fe3O4 impurity phase; electrochemical performance is significantly reduced, with a specific capacity of 98 mAh / g at 0.1C and a retention rate of only 78% after 500 cycles at 1C. This proves that the iron valence state is uniformly pure Fe. 3+ This is the core prerequisite for preparing pure-phase high-performance NFPP materials. Example

[0039] (1) Waste residue pretreatment: adjusting the Fe content of the leachate 3+Concentration 0.50 mol / L, P concentration 0.63 mol / L.

[0040] (2) Precipitation process: Precipitation temperature 80℃, pH=3.5~4.0, rapid addition of ammonium phosphate solution, aging for 1h, precursor Fe:P=3:3.98.

[0041] (3) Separation and drying: Same as in Example 1.

[0042] (4) Batching and molding: Add 15% of the precursor mass of citric acid as a carbon source, and 3% excess sodium carbonate. Spray dry the inlet temperature to 190°C, the outlet temperature to 105°C, and the feed rate to 8 mL / min.

[0043] (5) Calcination process: Calcination at 550℃ for 8 hours under argon atmosphere.

[0044] Performance testing: Initial specific capacity at 0.1C is 126mAh / g, capacity retention rate at 1C after 500 cycles is 96.2%, and specific capacity at 5C high rate is 108mAh / g. The synergistic effect of carbon coating and spherical structure results in the best overall performance of the material.

[0045] Comparative Example 3 NFPP material was prepared using analytical grade ferric phosphate, sodium carbonate, and glucose as raw materials, following the same process parameters as in Example 1.

[0046] Experimental results: The product is a pure-phase NFPP structure with a specific capacity of 127 mAh / g at 0.1C and a retention rate of 89.2% after 500 cycles at 1C. The electrochemical performance is basically the same as that of the process of this invention, but the raw material cost is 50% higher and there is no benefit of solid waste resource utilization, so it is impossible to achieve cost reduction and efficiency improvement and green production.

[0047] This invention encompasses any substitutions, modifications, equivalent methods, and solutions made within the spirit and scope of this invention. To provide the public with a thorough understanding of this invention, specific details are described in detail in the following preferred embodiments; however, those skilled in the art will fully understand the invention even without these details. Furthermore, to avoid unnecessary misunderstanding of the essence of this invention, well-known methods, processes, procedures, components, and circuits are not described in detail.

[0048] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing long-cycle polyanionic sodium cathode material from battery recycling, characterized in that, Using iron-phosphorus-containing waste residue from the acid leaching, impurity removal, and sodium carbonate precipitation recovery of lithium iron phosphate cathode material as raw material, Na4Fe3(PO4)2P2O7 sodium-ion battery cathode material is prepared, including the following steps: (1) Waste residue dissolution, impurity removal, and valence state control: The iron-phosphorus waste residue after lithium carbonate recovery is dissolved with inorganic acid, and an oxidant is added to remove Fe from the system. 2+ Completely oxidized to Fe 3+ Add soluble iron salts and phosphoric acid to regulate the initial concentrations of Fe and P in the system and inhibit the hydrolysis of iron ions; (2) Precipitation preparation of precursor by controlled precipitation: The oxidized leachate is heated to 40-80℃, a small amount of phosphoric acid is added as a stabilizer, and ammonium phosphate solution is slowly added dropwise under stirring. The pH of the system is adjusted to 2.0-4.0 by dilute ammonia or dilute acid. After the reaction is complete, the mixture is aged for 1-3 hours to generate ferric hydrogen phosphate precipitate with an iron-phosphorus molar ratio of 3:

4. (3) Precursor post-processing: The precipitated product was filtered, centrifuged, washed and dried to obtain high-purity ferric hydrogen phosphate precursor powder; (4) Batching, molding and sintering: The ferric hydrogen phosphate precursor, sodium carbonate and carbon source are mixed in proportion, water is added and sand milling is carried out to obtain a uniform slurry. The spherical precursor powder is prepared by spray drying and finally calcined at high temperature under an inert atmosphere to obtain pure phase Na4Fe3(PO4)2P2O7 cathode material.

2. The method according to claim 1, characterized in that, In step (1), the inorganic acid is hydrochloric acid or sulfuric acid; the oxidant is hydrogen peroxide, sodium hypochlorite or air; and the soluble iron salt is ferric sulfate or ferric nitrate.

3. The method according to claim 1, characterized in that, In step (2), the phosphoric acid added in advance is 85% concentrated phosphoric acid, and the amount added is 5% to 8% of the total phosphorus content of the leachate.

4. The method according to claim 1, characterized in that, In step (2), the concentration of ammonium phosphate solution is 1.0 mol / L, and the total amount added is 1.0 to 1.05 times the theoretical reaction amount.

5. The method according to claim 1, characterized in that, In step (4), the raw material ratios satisfy: Fe:P = 3:4, Na:Fe = 4:3, and the amount of sodium carbonate added is 1% to 3% excess of the theoretical stoichiometric ratio.

6. The method according to claim 1, characterized in that, In step (4), the carbon source is one or more of glucose, citric acid, ferric phosphate, and polyvinyl alcohol, and the amount of carbon source added is 10% to 15% of the mass of the ferric phosphate precursor.

7. The method according to claim 1, characterized in that, In step (4), the spray drying process parameters are: inlet temperature 180-190℃, outlet temperature 100-105℃, and feed rate 8-10mL / min.

8. The method according to claim 1, characterized in that, In step (4), the calcination atmosphere is argon, the heating rate is 5℃ / min, the calcination temperature is 550~700℃, and the holding time is 4~8h.

9. The Na4Fe3(PO4)2P2O7 cathode material prepared according to claim 1, characterized in that, The material has a pure polyionic structure, with a particle size of 200-500 nm and uniform particle size. Its initial specific capacity at 0.1C is 115-126 mAh / g, and its capacity retention rate is ≥90% after 500 cycles at 1C.